Toxic Relationship Representation and the Shifting Meaning of Love in TikTok Popular Culture - Ahmad Salman Farid (Feedback International Journal of Communication, 2025)
This study investigates how toxic romantic relationships are represented in TikTok videos and how these representations influence the evolving cultural meanings of love among young users. In the context of digital popular culture, TikTok has emerged as a key site for emotional storytelling and identity performance. Using a qualitative approach and Fairclough’s Critical Discourse Analysis (CDA), this study analyzed 50 viral TikTok videos and over 1,000 associated comments. Data were selected based on relational themes involving emotional manipulation, dependency, and conflict. The findings identify three dominant themes, (1) the romanticization of toxic behaviors, (2) the ironic or humorous reframing of emotional abuse, and (3) audience identification and normalization of harmful relationship dynamics. Users often interpret such content as relatable, aesthetic, or emotionally resonant. The study argues that TikTok functions not merely as a space of representation but as an emotional and cultural educator where toxic love is reframed and normalized. While some content invites critique, most contributes to shifting emotional norms. The research highlights the implications of these narratives on digital intimacy and the emotional expectations of youth.